Metabolic engineering of Cupriavidus necator H16 for the production of C5 platform chemicals - Gude, Christian (2021)
Raising demand for plastics, especially in developing countries, poses a challenge for suppliers to satisfy the need in a sustainable way. Developing carbon-neutral C5 platform chemicals for the production of easily recyclable biopolymers is an integral part of this mission. In this work, Cupriavidus necator H16 was metabolic engineered to produce the C5 precursors 5-aminovaleric acid and 5-hydroxyvaleric acid for plastic production from industrial waste gases. C. necator H16 was selected as host organism for metabolic engineering because of its ability to grow lithoautotrophically, using CO2 waste gas as carbon source, ammonia as nitrogen source and hydrogen as energy source.